CONTROVERSY OF ACTIVITY-BASED COSTING: EFFICIENCY OR COST-SAVING DISTORTION? A CONTINGENCY THEORY PERSPECTIVE - Mukhtaruddin; Amelia Putri Nur (Jurnal Manajemen Perbankan Keuangan Nitro, 2026)
Activity-Based Costing (ABC) is a cost accounting system designed to produce more accurate cost information by tracing costs based on activities. Although ABC is considered superior to traditional costing systems, its implementation in manufacturing companies still faces various challenges. This study aims to examine the challenges of implementing ABC in manufacturing companies from the perspective of contingency theory. The research method used is a literature review by analyzing relevant journals and scientific publications published between 2021 and 2026. The results of the review indicate that the main challenges in implementing ABC in manufacturing companies include the complexity of identifying activities and cost drivers, high data requirements, substantial implementation costs, limitations in accounting information systems, and employee resistance to changes in the costing system. Based on contingency theory, these challenges arise due to a mismatch between the characteristics of manufacturing companies—such as company size, the level of complexity in production processes, and the readiness of organizational resources—and the requirements of the ABC system within organizational conditions. This study is expected to provide conceptual insights for manufacturing companies when considering the effective implementation of ABC.